Arabic Language as the Icon of Islamic Higher Education: A Study of the Implementation of Arabic Intensive Program - Warnis Warnis; Hetti Waluati Triana; Martin Kustati; Remiswal Remiswal; Nelmawarni Nelmawarni (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2019)
AbstractArabic intensive Program is important to improve the quality of foreign language ability for UIN Imam Bonjol students. The planning, implementing and evaluating the process of the Arabic Intensive Program needs to be addressed and improved from various aspects. Thus, the study aims to identify appropriate policies to improve the management of the Intensive Arabic Language program, to develop Arabic language competency standards based on an analysis of the real conditions of the main components and program supporters, and to formulate the standard to improve the quality of Arabic Intensive Programs at UIN Imam Bonjol, Padang. This study used a qualitative approach where the data taken from interviews, documentation and focus group discussion. Data sources are managers, lecturers, and students participating in Arabic Intensive Program. The results of the study showed that the Arabic programs need appropriate policies to overcome the obstacles and problems. The visible problems were in the planning process, especially planning in the learning objectives, materials, and the provision of lecturers; In connection with the implementation of Arabic Intensive programs, there are still constrained by the available facilities and infrastructure, related to evaluation, the results of the study show that comprehensive evaluation needs to be done in relation to the evaluation of inputs, processes, outputs, and impacts to improve the quality of Arabic as an institutional brand in the future..AbstrakProgram intensif bahasa Arab penting untuk meningkatkan kualitas kemampuan bahasa asing bagi siswa UIN Imam Bonjol. Perencanaan, implementasi dan evaluasi proses Program Intensif Arab perlu ditangani dan ditingkatkan dari berbagai aspek. Dengan demikian, penelitian ini bertujuan untuk mengidentifikasi kebijakan yang tepat untuk meningkatkan manajemen program Bahasa Arab Intensif, untuk mengembangkan standar kompetensi bahasa Arab berdasarkan analisis kondisi nyata dari komponen utama dan pendukung program, dan untuk merumuskan standar untuk meningkatkan kualitas Program Intensif Bahasa Arab di UIN Imam Bonjol, Padang. Penelitian ini menggunakan pendekatan kualitatif dimana data diambil dari wawancara, dokumentasi dan diskusi kelompok terarah. Sumber data adalah pimpinan, dosen, dan mahasiswa yang berpartisipasi dalam Program Intensif Arab. Hasil penelitian menunjukkan bahwa program-program Arab membutuhkan kebijakan yang tepat untuk mengatasi hambatan dan masalah. Masalah yang terlihat dalam proses perencanaan, terutama perencanaan dalam tujuan pembelajaran, bahan, dan penyediaan dosen; Sehubungan dengan pelaksanaan program-program Intensif Bahasa Arab, masih ada kendala oleh fasilitas dan infrastruktur yang tersedia, terkait dengan evaluasi, hasil penelitian menunjukkan bahwa evaluasi komprehensif perlu dilakukan sehubungan dengan evaluasi input, proses, output, dan dampak untuk meningkatkan kualitas bahasa Arab sebagai merek kelembagaan di masa depan. How to Cite : Warnis, Triana, H. W., Remiswal, Kustati, M., Nelmawarni. (2019). Arabic Language as the Icon of Islamic Higher Education: A Study of the Implementation of Arabic Intensive Program. TARBIYA: Journal of Education in Muslim Society, 6(1), 102-115. doi:10.15408/tjems.v6i1. 10910.